Innovative research on college English grammar teaching and the introduction of sustainable education concept from the perspective of linguistics: An analysis using PLS-SEM algorithm - Xuan, Gang; Han, Bing; Wang, Dan (Journal of computational methods in sciences and engineering, 2025)
The study aims to explore the impact of sustainable education concepts and linguistic perspectives on innovation in teaching and learning English grammar at university. By constructing a university English grammar teaching program based on six strategies, the effects of antecedent, mediator, and outcome variables on teaching innovation were analyzed and five hypotheses about the interactions of these variables were formulated. The model was validated using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) algorithm. The predictive power of models 1–3 on teaching innovation was 0.024, 0.046, and 0.607, respectively. Expressive ability, language culture, internal and external classroom environment, and teaching style all positively influenced teaching innovation, with regression coefficients of 0.436, 0.061, −0.146, and 0.396, respectively. But the expressive ability and teaching style were significant, while the remaining two dimensions were not significant. The results of the path analysis showed that all the hypotheses in the model were tested and the path coefficients obtained from the test, and the corresponding chi-square significance coefficients met the requirements. The study enriches the theory of pedagogical innovation and exposes the role of the joint linguistic perspective of sustainable education on pedagogical innovation.